Black aluminum oxide ceramic component with improved antistatic function and preparation method thereof

By optimizing the raw materials and process conditions of black alumina ceramics, black alumina ceramic components with low light reflectivity and excellent physical properties were prepared, and their anti-static functions were improved through the sintering step, the preparation of black alumina ceramics in the prior art was solved. Component problems and electrostatic imbalance problems.

CN119430874APending Publication Date: 2025-02-14NICE INFORMATION SERVICES CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202311341925.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-08-04
Filing Date
2023-10-17
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The prior art is difficult to prepare black alumina ceramic components with low light reflectivity, black color and excellent physical properties, while there is a problem of electrostatic imbalance in the semiconductor/display manufacturing process, resulting in wafer sliding.

Method used

By optimizing the composition and content of black alumina ceramic raw materials, combined with ball milling, stirring, molding, drying and sintering processes, black alumina ceramic parts with low light reflectivity and excellent physical properties were prepared, and sintered by gradual heating and cooling Steps to improve its yield and anti-static function.

Benefits of technology

It realizes excellent performances such as low light reflectivity, chemical resistance, chemical stability, heat resistance and insulation of black alumina ceramic components, and at the same time significantly improves its anti-static function, reduces sintering defects, and increases yield .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430874A_ABST
    Figure CN119430874A_ABST
Patent Text Reader

Abstract

The anti-static function of the black aluminum oxide ceramic component is improved. The black alumina ceramic member with improved antistatic function according to an exemplary embodiment of the present invention can be prepared by combining 100 parts by weight of a black alumina ceramic raw material, 56.4 to 76.8 parts by weight of an additive, and 9.5 to 12.5 parts by weight of a binder, the black alumina ceramic raw material having a particle size of 1 to 10 micrometers, the additive having a particle size of 1 to 10 micrometers, and the binder having a particle size of 1 to 10 micrometers. The present invention relates to a ceramic material, which may include 56.4 to 76.6 wt% of aluminum oxide (Al2O3), and 23.4 to 43.6 wt% of a colorant, which may be composed of 8.0 to 15.0 wt% of Co2O3, 6.0 to 10.0 wt% of Fe2O3, 4.0 to 7.0 wt% of TiO2, 3.4 to 8.0 wt% of MnO2, 0.5 to 0.8 wt% of ZnO, 1.0 to 2.0 wt% of SiO2, and 0.5 to 0.8 wt% of ZrO2.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a black alumina ceramic component with improved antistatic function and a preparation method thereof. More specifically, the present invention relates to a method for preparing a black alumina ceramic component with improved antistatic function by subjecting a black alumina ceramic raw material to a ball milling process, a stirring process, a molding process, a drying process, and a sintering process under optimal conditions, thereby minimizing the defective rate of bending, cracking, bubbles, etc., increasing the yield, and improving the antistatic function of the final product, and a black alumina ceramic component with improved antistatic function prepared by the method. Background Art

[0002] Photolithography is a technology that uses light to transfer a desired circuit design onto a wafer for replication. It is a very important process for forming a pattern designed in semiconductor manufacturing processes and display manufacturing processes on the wafer. It leads the miniaturization of semiconductors and can be regarded as a process that requires high accuracy in patterning.

[0003] However, the general alumina (Al2O3) ceramics used in the manufacturing process of such semiconductors and displays are ivory or white in color and therefore have high light reflectivity, but the more sophisticated the process, the lower the precision.

[0004] For the above reasons, a black alumina material capable of absorbing light, having low insulation resistance, and having high bending strength is required, but in Korea, a black alumina material has not been commercialized and a method for preparing a black alumina ceramic part has not been established.

[0005] Generally speaking, Zn-Al-Cr-Fe spinel pigments are ceramic pigments that present various tones. 3+ Cr 3+ , Fe 3+ The content of can produce yellow, red, and black ceramics. In particular, as a composition showing black, there is an α-Al2O3 type solid solution of (Cr, Fe)2O3, but it is reported that (Co, Ni)O-(Cr, Fe)2O3 type spinel is suitable for high temperature, and the addition of Ti or Mn type oxides is also used for black expression. In addition, there is a method of blackening alumina by preventing carbon oxidation in a vacuum atmosphere and then impregnating it, but this process has not yet been established and has not been promoted.

[0006] Japanese Patent No. 6141756 (Prior Patent 1) and Korean Patent No. 1168863 disclose technical contents related to ceramic vacuum chucks with low reflectivity or containing colorants, but no specific technology that can simultaneously optimize processability and reflectivity has been disclosed.

[0007] As mentioned above, since the preparation method of black alumina ceramic parts should have the same or similar physical properties as general alumina ceramics, and need to show black or near-black color, a more precise and detailed process is required, but the detailed conditions of the related process have not yet been promoted.

[0008] On the other hand, when black alumina ceramic components are applied to wafer manufacturing equipment used in the manufacturing process of semiconductors / displays, such as vacuum chucks, electrostatic chucks, etc., when clamping the semiconductor / display wafer, instantaneous unbalanced static electricity may be generated between the front side of the vacuum chuck or the electrostatic chuck and the back side of the wafer. This unbalanced static electricity may cause the semiconductor wafer to slip during the process of fixing the semiconductor / display wafer. In order to solve these problems, there is an urgent need to develop a black alumina ceramic component with improved anti-static function. Summary of the invention

[0009] An object of the present invention is to provide a black alumina ceramic component having low light reflectivity by showing a black or even nearly black color and a method for preparing the same.

[0010] Another object of the present invention is to provide a method for preparing a black alumina ceramic component that can minimize sintering defects such as bending, cracks and bubbles by optimizing specific process conditions.

[0011] Still another object of the present invention is to provide a method for preparing a black alumina ceramic component with improved yield through a plurality of sintering steps sequentially performed through a gradual temperature increase process and a gradual cooling process.

[0012] Another object of the present invention is to provide a black alumina ceramic component and a preparation method thereof, wherein the antistatic function is improved by optimizing the composition and content ratio of the raw materials and adjusting the specific conditions of the preparation process using the raw materials.

[0013] According to an exemplary embodiment of the present invention, a method for preparing a black alumina ceramic component with improved antistatic function may include: a raw material preparation step of combining black alumina ceramic raw materials; a ball milling step of adding additives to the black alumina ceramic raw materials and then crushing them to prepare black alumina ceramic powder; a stirring step of stirring the black alumina ceramic powder and a binder; a molding step of filling the stirred black alumina ceramic powder into a mold and then pressurizing it to form a molded body; a drying step of drying the molded body; and a sintering step of heating the dried molded body, cooling it and sintering it. At this time, in the raw material preparation step, the black alumina ceramic raw material is prepared by mixing 56.4 to 76.6 weight % of alumina (Al2O3) and 23.4 to 43.6 weight % of a colorant, and the colorant may be composed of 8.0 to 15.0 weight % of Co2O3, 6.0 to 10.0 weight % of Fe2O3, 4.0 to 7.0 weight % of TiO2, 3.4 to 8.0 weight % of MnO2, 0.5 to 0.8 weight % of ZnO, 1.0 to 2.0 weight % of SiO2, and 0.5 to 0.8 weight % of ZrO2.

[0014] The ball milling step may be performed by adding 56.4 to 76.8 parts by weight of the additive to 100 parts by weight of the black alumina ceramic raw material and then pulverizing the raw material.

[0015] The additive may be composed of 55 to 75 parts by weight of water (H2O) and 1.4 to 1.8 parts by weight of a dispersant relative to 100 parts by weight of the black alumina ceramic raw material.

[0016] The stirring step may be performed by adding 9.5 to 12.5 parts by weight of a binder to 100 parts by weight of the black alumina ceramic powder and then stirring.

[0017] The binder may be composed of 9 to 11 parts by weight of PVA and 0.5 to 1.5 parts by weight of PEG relative to 100 parts by weight of the black alumina ceramic powder.

[0018] The sintering step may include: a first sintering step performed by raising the temperature from 0°C to 1390°C; a second sintering step performed by maintaining the temperature at a maximum temperature of 1390°C; and a third sintering step performed by reducing the temperature from 1390°C to 650°C.

[0019] The first sintering step may include first to fifth temperature maintaining steps of maintaining the temperature at 100° C., 250° C., 400° C., 800° C., and 1100° C. for specific time periods, respectively.

[0020] The second sintering step may be performed for 4 to 6 hours.

[0021] The third sintering step may include a sixth temperature maintaining step of maintaining the temperature at 1100° C. for a specific time.

[0022] According to an exemplary embodiment of the present invention, a black alumina ceramic component with improved antistatic function can be prepared by combining 100 weight parts of a black alumina ceramic raw material; 56.4 to 76.8 weight parts of an additive; and 9.5 to 12.5 weight parts of a binder; the black alumina ceramic raw material includes: 56.4 to 76.6 weight% of aluminum oxide (Al2O3); and 23.4 to 43.6 weight% of a colorant; the colorant is composed of 8.0 to 15.0 weight% of Co2O3, 6.0 to 10.0 weight% of Fe2O3, 4.0 to 7.0 weight% of TiO2, 3.4 to 8.0 weight% of MnO2, 0.5 to 0.8 weight% of ZnO, 1.0 to 2.0 weight% of SiO2, and 0.5 to 0.8 weight% of ZrO2.

[0023] Effects of the Invention

[0024] According to the method for preparing a black alumina ceramic component with improved antistatic function of an exemplary embodiment of the present invention, by showing a black or even close to black color, a black alumina ceramic component with low light reflectivity and excellent physical properties such as chemical resistance, chemical stability, heat resistance, and insulation can be prepared.

[0025] At this time, each specific process condition of the raw material preparation step, ball milling step, stirring step, molding step, drying step, and sintering step included in the preparation method of the black alumina ceramic component with improved anti-static function can be optimized, so the sintering defects of the black alumina ceramic component such as bending, cracks, bubbles, etc. can be minimized.

[0026] In addition, the sintering step may include a plurality of sintering steps sequentially performed through a gradual heating process and a gradual cooling process, thereby greatly improving the physical properties and yield of the ultimately produced black alumina ceramic component.

[0027] In addition, by optimizing the composition and content of the raw materials for preparing the black alumina ceramic component and adjusting the temperature conditions and execution time of the sintering process during the preparation process, the anti-static function of the finally prepared black alumina ceramic component is significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1is a flowchart for explaining a method for preparing a black alumina ceramic component having an improved antistatic function according to an exemplary embodiment of the present invention.

[0029] Figure 2 is a flowchart for explaining a sintering step of a black alumina ceramic component having an improved antistatic function according to an exemplary embodiment of the present invention. DETAILED DESCRIPTION

[0030] The following is a description of the specific implementation of the present invention. The following specific description is provided to help a comprehensive understanding of the methods, devices and / or systems described in this specification. However, these are only examples, and the present invention is not limited thereto.

[0031] When describing an embodiment of the present invention, when it is judged that the specific description of the known technology related to the present invention will make the gist of the present invention unclear, its detailed description will be omitted. In addition, the terms described below are terms defined in consideration of the functions in the present invention, which can be changed according to the intention or habit of the user or operator. Therefore, the definition should be defined based on the content in the entire specification. The terms used in the detailed description are only used to describe embodiments of the present invention, and are not restrictive. Unless otherwise clearly used, the expression in the singular includes the meaning of the plural form. In this specification, expressions such as "including" or "having" should be interpreted as referring to certain characteristics, numbers, steps, actions, elements, parts or combinations of these, and do not exclude the existence or possibility of more than one other characteristics, numbers, steps, actions, elements, parts or combinations of these other than those mentioned.

[0032] In addition, when describing the components of the embodiments of the present invention, terms such as first, second, A, B, (a), (b), etc. may be used. These terms are only used to distinguish the components from other components, and the nature, order, sequence, etc. of the components are not limited by these terms.

[0033] Figure 1 is a flowchart for explaining a method for preparing a black alumina ceramic component having an improved antistatic function according to an exemplary embodiment of the present invention.

[0034] Reference Figure 1According to an exemplary embodiment of the present invention, a method for preparing a black alumina ceramic component with improved antistatic function may include: a raw material preparation step (S1), combining black alumina ceramic raw materials; a ball milling step (S2), crushing the black alumina ceramic raw materials together with additives to prepare black alumina ceramic powder; a stirring step (S3), stirring the black alumina ceramic powder and a binder; a molding step (S4), filling the stirred black alumina ceramic powder into a mold, and then pressurizing it to form a molded body; a drying step (S5), drying the molded body; and a sintering step (S6), heating the dried molded body, cooling it, and sintering it.

[0035] In an exemplary embodiment, in the raw material preparation step (S1), the black alumina ceramic raw material may be prepared by mixing 23.4 to 43.6 wt % of a colorant with 56.4 to 76.6 wt % of alumina (Al2O3).

[0036] At this time, when the content of alumina contained in the black alumina ceramic raw material is less than 56.4 weight %, the physical properties of the finally prepared black alumina ceramic component may be reduced, and when the content of alumina contained in the black alumina ceramic raw material exceeds 76.6 weight %, it may not be able to properly express black or even a color close to black, and therefore, the light reflectivity may increase.

[0037] That is, when the content of the colorant exceeds 43.6 wt %, the physical properties of the finally prepared black alumina ceramic component may be reduced, and when the content of the colorant is less than 23.4 wt %, the black or even near-black color cannot be properly expressed, and therefore, the light reflectivity of the finally prepared black alumina ceramic component may increase.

[0038] In one embodiment, the colorant may be composed of 8.0 to 15.0 wt % Co2O3, 6.0 to 10.0 wt % Fe2O3, 4.0 to 7.0 wt % TiO2, 3.4 to 8.0 wt % MnO2, 0.5 to 0.8 wt % ZnO, 1.0 to 2.0 wt % SiO2, and 0.5 to 0.8 wt % ZrO2.

[0039] Among the components contained in the colorant, when the content of Co2O3, Fe2O3, TiO2 and MnO2 is less than the above-mentioned numerical range, the prepared black alumina ceramic component cannot show an appropriate color, and the light reflectivity may increase. Among the components contained in the colorant, when the content of Co2O3, Fe2O3, TiO2 and MnO2 exceeds the above-mentioned numerical range, the physical properties of the prepared black alumina ceramic component may be reduced.

[0040] In addition, when the content of ZnO in the components included in the colorant is less than the above numerical range or exceeds the above numerical range, cracks may appear in the prepared black alumina ceramics, and when the content of ZnO in the components included in the colorant is less than the above numerical range or exceeds the above numerical range, the theoretical density of the prepared black alumina ceramic parts may be relatively lower than that of fine alumina ceramics, and sintering defects such as bending, cracks, bubbles, etc. may occur.

[0041] In addition, when the content of SiO2 and ZrO2 in the components included in the colorant is less than the above numerical range or exceeds the above numerical range, cracks may appear in the finally prepared black alumina ceramic parts, or the theoretical density of the prepared black alumina ceramic parts may be relatively lower than that of fine alumina ceramics, and sintering defects such as bending, cracks, bubbles, etc. may occur.

[0042] After the raw material preparation step (S1) is completed, a ball milling step (S2) may be performed, that is, the black alumina ceramic raw material is added with additives and then pulverized to prepare black alumina ceramic powder.

[0043] In an exemplary embodiment, the ball milling step (S2) may be performed by adding 56.4 to 76.8 parts by weight of the additive with respect to 100 parts by weight of the black alumina ceramic raw material and then pulverizing the additive.

[0044] In one embodiment, the additive may be composed of water (H2O) and a dispersant. The additive, relative to 100 parts by weight of the black alumina ceramic raw material, may be composed of 55 to 75 parts by weight of water (H2O) and 1.4 to 1.8 parts by weight of a dispersant. Preferably, the additive may be composed of 60 to 70 parts by weight of water (H2O) and 1.5 to 1.7 parts by weight of a dispersant.

[0045] At this time, the dispersant is a composition added to make the black alumina ceramic raw material of the solid component and the additive of the liquid component dispersed well, and at least one dispersant selected from the group consisting of anionic compounds, cationic compounds, nonionic compounds and polymer compounds can be used. The dispersant can use an aqueous dispersant, for example, anionic (Anionic) type, nonionic (Non-ionic) type, polycarboxylic acid (Polycarboxylicacid) type, polycarboxylic acid amine salt (Polycarboxylic acid amine salt) type, polycarboxylic acid ammonium salt (Polycarboxylic acid ammonium salt) type, polycarboxylic acid sodium salt (Polycarboxylic acid sodiumsalt) type, polyester polyester (Polyester Polyester) type dispersant. However, the concept of the present invention is not necessarily limited to this, and the dispersant can also use, for example, a polyethylene oil-based dispersant.

[0046] Specifically, the ball milling step (S2) is performed as follows: the alumina or alumina (Al2O3) balls prepared by the raw material preparation step (S1), that is, the balls made of the black alumina ceramic raw material, are supplied to the ball mill, accounting for 50% to 70% of the volume of the ball mill, the additive is added to the remaining volume of the ball mill, and then the driving speed of the ball mill is set to 45rpm to 55rpm, preferably set to 48rpm and then driven.

[0047] In an exemplary embodiment, the particle size of the black alumina ceramic powder prepared in the ball milling step (S2) may be 0.109 μm to 0.153 μm. At this time, when the particle size of the black alumina ceramic powder is less than 0.109 μm, the physical properties of the finally prepared black alumina ceramic component may be reduced, and when the particle size of the black alumina ceramic powder is greater than 0.153 μm, the light reflectivity of the finally prepared black alumina ceramic component may become high, or sintering defects such as bending, cracks, bubbles, etc. may occur.

[0048] In an exemplary embodiment, the ball milling step (S2) may be performed by driving the ball milling device for 15 to 20 hours. At this time, when the driving time of the ball milling device is less than 15 hours, the physical properties of the finally prepared black alumina ceramic component may be reduced, and when the driving time of the ball milling device exceeds 20 hours, the light reflectivity of the finally prepared black alumina ceramic component may become high, or sintering defects such as bending, cracks, bubbles, etc. may occur.

[0049] After the ball milling step (S2) is completed, the stirring step (S3) of stirring the black alumina ceramic powder with a binder, the molding step (S4) of filling the stirred black alumina ceramic powder into a mold and press-molding, and the drying step (S5) of drying the black alumina molded body can be performed in sequence.

[0050] The stirring step (S3) can be performed by mixing the black alumina ceramic powder and the binder and introducing the mixture into a pressurized tank, and setting the stirrer installed in the pressurized tank to a rotation speed of 30 rpm and driving the mixture for 48 hours.

[0051] In an exemplary embodiment, the stirring step (S3) may be performed by adding 9.5 to 12.5 parts by weight of a binder relative to 100 parts by weight of the black alumina ceramic powder and then stirring. In one embodiment, the binder may be composed of 9 to 11 parts by weight of PVA and 0.5 to 1.5 parts by weight of PEG relative to 100 parts by weight of the black alumina ceramic powder.

[0052] The molding step (S4) can be performed as follows; that is, after assembling a mold that meets the specifications, the mold is tilted 45°, and then the pressure of the pressurized tank is set to 3kg / mpa. After the black alumina ceramic powder mixed with the binder is filled into the mold, the mold is kept horizontal. After 48 hours, the molded body is separated from the mold and naturally dried for 24 hours.

[0053] The drying step (S5) can be performed as follows: after the naturally dried molded body is dried in a constant temperature and humidity drying room set at an internal humidity of 80% and an internal temperature of 28°C for 10 to 15 days, the molded body that has been subjected to the constant temperature and humidity drying is dried in a hot drying room set at an internal temperature of 40°C to 50°C for 2 to 3 days.

[0054] At this time, the constant temperature and humidity drying step and the heat drying step may be performed sequentially.

[0055] The sintering step (S6) may be performed after the drying step (S5), and the overall process of the sintering step (S6) is shown in Table 1 below.

[0056]

Table 1

[0057]

[0058] Figure 2 is a flowchart for explaining a sintering step of a black alumina ceramic component according to an exemplary embodiment of the present invention.

[0059] Also refer to Table 1 and Figure 2 The sintering step (S6) may include: a first sintering step (S61) in which the temperature is gradually increased from 0°C to 1390°C; a second sintering step (S62) in which the temperature is maintained at a maximum temperature of 1390°C; and a third sintering step (S63) in which the temperature is gradually reduced from 1390°C to 650°C.

[0060] The first sintering step (S61) may include: a first heating interval of heating the temperature from 0°C to 100°C, a second heating interval of heating the temperature from 100°C to 250°C, a third heating interval of heating the temperature from 250°C to 400°C, a fourth heating interval of heating the temperature from 400°C to 800°C, a fifth heating interval of heating the temperature from 800°C to 1100°C, and a sixth heating interval of heating the temperature from 1100°C to 1390°C.

[0061] The first heating interval can be performed for about 24 hours, the second heating interval can be performed for about 96 hours, the third heating interval can be performed for about 120 hours, the fourth heating interval can be performed for about 96 hours, the fifth heating interval can be performed for about 48 hours, and the sixth heating interval can be performed for about 30 hours.

[0062] The first temperature rise interval may be an interval for adding moisture, the second temperature rise interval may be an interval for degreasing the dispersant, and the third temperature rise interval may be an interval for degreasing the added component. The fourth temperature rise interval may be an interval for oxidation and removal of carbon to carbon components, the fifth temperature rise interval may be an interval for the first shrinkage of the product, and the sixth temperature rise interval may be an interval for the second shrinkage of the product. At this time, the fifth temperature rise interval may be called the first shrinkage step, and the sixth temperature rise interval may be called the second shrinkage step.

[0063] The first sintering step ( S61 ) may further include a temperature maintaining step for maintaining the temperature between the first temperature increasing section to the sixth temperature increasing section for a predetermined time.

[0064] In an exemplary embodiment, a first temperature maintaining step of maintaining a temperature of about 100° C. for about 2 hours may be performed between the first temperature increasing interval and the second temperature increasing interval, a second temperature maintaining step of maintaining a temperature of about 250° C. for about 2 hours may be performed between the second temperature increasing interval and the third temperature increasing interval, and a third temperature maintaining step of maintaining a temperature of about 400° C. for about 4 hours may be performed between the third temperature increasing interval and the fourth temperature increasing interval, a fourth temperature maintaining step of maintaining a temperature of about 800° C. for about 2 hours may be performed between the fourth temperature increasing interval and the fifth temperature increasing interval, and a fifth temperature maintaining step of maintaining a temperature of about 1100° C. for about 2 hours may be performed between the fifth temperature increasing interval and the sixth temperature increasing interval. After the sixth temperature increasing interval, a second sintering step (S62) performed by maintaining a maximum temperature of 1390° C. may be performed.

[0065] At this time, the first temperature holding interval may be an interval for forming the inner line of the molded body, the second temperature holding interval may be an interval for degreasing the dispersant and forming the overall line, the third temperature holding interval may be an interval for removing the residual binder, the fourth temperature holding interval may be an interval for removing the residual carbon or carbon components, and the fifth temperature holding interval may be an interval for more smoothly performing the first shrinkage of the product. At this time, the third temperature holding interval may also be called a binder removal step.

[0066] The second sintering step (S62) may be a step for completing the second shrinkage of the product while completing the physical properties of the product.

[0067] On the other hand, when the sintering step is performed at a temperature above 1400°C which is set as the existing peak temperature, if the finally prepared black alumina ceramic component is used for a wafer chuck for semiconductor / display manufacturing, static electricity and other problems may occur, resulting in a decrease in the anti-static function. In order to solve the problem, a process of adjusting the peak temperature in the sintering step (S6) of the present invention is performed. Through various peak temperature deformation experiments, a peak temperature of 1390°C is set that can maximize the anti-static function of the finally prepared alumina ceramic component while increasing the yield.

[0068] The results confirmed that although the temperature difference between the existing peak temperature and the peak temperature of the present invention is only 10°C, which is not much, according to the execution of the second sintering step (S2), that is, the temperature does not drop immediately from the peak temperature but is maintained for a specific time, the anti-static function and yield of the black alumina ceramic parts finally prepared are very different. The specific experimental results are shown in Table 2 below.

[0069]

Table 2

[0070] Sintering peak temperature (℃) Surface resistance (ohm / sq) Example 1390 <![CDATA[10 6 Up to 10 9 ]]> Comparative Example 1 1400 <![CDATA[10 12 ]]> Comparative Example 2 1390 <![CDATA[10 14 ]]> Comparative Example 3 1390 <![CDATA[10 11 ]]> Comparative Example 4 1390 <![CDATA[10 10 ]]>

[0071] At this time, the embodiment of the present invention uses a vacuum chuck of a ceramic component prepared by setting the sintering peak temperature to 1390°C using the above raw material composition and content ratio, while Comparative Example 1 uses a vacuum chuck of a holding component prepared by setting the sintering temperature to 1400°C using the same raw material composition and content ratio as the above embodiment. Comparative Examples 2 and 3 use vacuum chucks using a ceramic component prepared as follows, that is, the sintering peak temperature of the ceramic component is set to 1390°C, the same as the above embodiment, but the raw material composition and content ratio are different from the above embodiment. Specifically, Comparative Example 2 uses a vacuum chuck prepared based on the black ceramic (Black Ceramic) (JP7242699B2) formula of Kyocera Corporation of Japan, and Comparative Example 3 uses a vacuum chuck prepared based on the black alumina ceramic preparation method (KR 2023-0064673A) of the same company. Comparative Example 4 uses a vacuum suction cup using a ceramic component prepared as follows. The ceramic component is prepared using the same manufacturing raw material composition and content ratio as the above-mentioned embodiment, and the sintering peak temperature is set to 1390°C. Among them, the second heating interval, the third heating interval and the fourth heating interval are executed for 48 hours, 96 hours and 48 hours respectively to prepare the ceramic component.

[0072] As shown in Table 2, it was confirmed that Comparative Examples 1 to 4 had higher surface resistance values ​​than the examples of the present invention, and thus it was confirmed that the antistatic function of the vacuum chuck using the ceramic component finally prepared by the examples of the present invention was significantly improved.

[0073] After the first sintering step ( S61 ) and the second sintering step ( S62 ) are completed, a third sintering step ( S63 ) performed by lowering the temperature from 1390° C. to 650° C. may be performed.

[0074] The third sintering step (S63) may include: a first temperature reduction interval in which the temperature is reduced from 1390°C to 1100°C; and a second temperature reduction interval in which the temperature is reduced from 1100°C to 650°C, and a sixth temperature maintenance step in which the temperature of 1100°C is maintained for about 1 hour may be performed between the first temperature reduction interval and the second temperature reduction interval. In this case, the sixth temperature maintenance step may be used to suppress the occurrence of stress caused by rapid cooling of the product.

[0075] After the sintering step (S6) is performed, the processing step (S7) can be performed in various ways according to the purpose, application, function, etc. of the final product. When the processing step (S7) is completed, the preparation of the black alumina ceramic component can be completed.

[0076] As described above, the method for preparing a black alumina ceramic component according to an exemplary embodiment of the present invention includes: a raw material preparation step (S1), a ball milling step (S2), a stirring step (S3), a molding step (S4), a drying step (S5) and a sintering step (S6). Since the specific process conditions of each step can be optimized, a black alumina ceramic having a low light reflectivity and excellent physical properties such as chemical resistance, chemical stability, heat resistance, and insulation can be prepared by showing a black or even nearly black color. In addition, sintering defects such as bending, cracks, and bubbles of the finally prepared black alumina ceramic component can be minimized.

[0077] In particular, the sintering step (S6) may include a plurality of sintering steps sequentially performed through a gradual temperature increase process and a gradual cooling process, thereby greatly improving the yield of the black alumina ceramic component.

[0078] In addition, by optimizing the composition and content of the raw materials for preparing the black alumina ceramic component and adjusting the temperature conditions and execution time of the sintering process in the preparation process, the anti-static function of the finally prepared black alumina ceramic component is significantly improved.

[0079] However, the concept of the present invention is not necessarily limited thereto, and the method according to the exemplary embodiment of the present invention may be applied to various product / technical fields other than the above-mentioned product / technical fields.

[0080] Although various embodiments of the present invention have been described in detail above, it should be understood by those skilled in the art that various modifications may be made to the above embodiments without departing from the scope of the present invention. Therefore, the scope of the present invention should not be limited to the described embodiments, but should be determined by the claims and their equivalents.

Claims

1. A method for preparing a black alumina ceramic component with improved antistatic function, characterized in that: include: A raw material preparation step, combining black alumina ceramic raw materials; A ball milling step, wherein an additive is added to the black alumina ceramic raw material and then the raw material is crushed to prepare a black alumina ceramic powder; A stirring step, stirring the black alumina ceramic powder and the binder; A molding step, filling the stirred black alumina ceramic powder into a mold, and then pressurizing to form a molded body; A drying step, drying the molded body; as well as a sintering step, heating the dried molded body, cooling it, and sintering it, In the raw material preparation step, the black alumina ceramic raw material is prepared by mixing 56.4 to 76.6 wt % of alumina (Al2O3) and 23.4 to 43.6 wt % of a colorant. The colorant consists of 8.0 to 15.0 wt % Co2O3, 6.0 to 10.0 wt % Fe2O3, 4.0 to 7.0 wt % TiO2, 3.4 to 8.0 wt % MnO2, 0.5 to 0.8 wt % ZnO, 1.0 to 2.0 wt % SiO2, and 0.5 to 0.8 wt % ZrO2.

2. The method for preparing a black alumina ceramic component with improved antistatic function according to claim 1, characterized in that: The ball milling step is performed by adding 56.4 to 76.8 parts by weight of an additive to 100 parts by weight of the black alumina ceramic raw material and then pulverizing the raw material.

3. The method for preparing a black alumina ceramic component with improved antistatic function according to claim 2, characterized in that: The additive comprises 55 to 75 parts by weight of water (H2O) and 1.4 to 1.8 parts by weight of a dispersant relative to 100 parts by weight of the black alumina ceramic raw material.

4. The method for preparing a black alumina ceramic component with improved antistatic function according to claim 1, characterized in that: The stirring step is performed by adding 9.5 to 12.5 parts by weight of a binder to 100 parts by weight of the black alumina ceramic powder and stirring the mixture.

5. The method for preparing a black alumina ceramic component with improved antistatic function according to claim 1, characterized in that: The binder is composed of 9 to 11 parts by weight of PVA and 0.5 to 1.5 parts by weight of PEG relative to 100 parts by weight of the black alumina ceramic powder.

6. The method for preparing a black alumina ceramic component with improved antistatic function according to claim 1, characterized in that: The sintering step comprises: A first sintering step performed by increasing the temperature from 0°C to 1390°C; A second sintering step performed by maintaining the temperature at a maximum temperature of 1390°C; and The third sintering step was performed by lowering the temperature from 1390°C to 650°C.

7. The method for preparing a black alumina ceramic component with improved antistatic function according to claim 6, characterized in that: The first sintering step includes first to fifth temperature keeping steps of keeping the temperature at 100° C., 250° C., 400° C., 800° C. and 1100° C. for a specific time, respectively.

8. The method for preparing a black alumina ceramic component with improved antistatic function according to claim 6, characterized in that: The second sintering step is performed for 4 to 6 hours.

9. The method for preparing a black alumina ceramic component with improved antistatic function according to claim 6, characterized in that: The third sintering step includes a sixth temperature maintaining step of maintaining the temperature at 1100° C. for a specific time.

10. A black alumina ceramic component with improved antistatic function, characterized in that: The black alumina ceramic component is prepared by mixing 100 parts by weight of a black alumina ceramic raw material; 56.4 to 76.8 parts by weight of additives; and 9.5 to 12.5 parts by weight of a binder; The black alumina ceramic raw material comprises: 56.4 to 76.6 weight percent aluminum oxide (Al2O3); and 23.4 to 43.6 wt % colorant; The colorant consists of 8.0 to 15.0 wt % Co2O3, 6.0 to 10.0 wt % Fe2O3, 4.0 to 7.0 wt % TiO2, 3.4 to 8.0 wt % MnO2, 0.5 to 0.8 wt % ZnO, 1.0 to 2.0 wt % SiO2, and 0.5 to 0.8 wt % ZrO2.

Citation Information

Patent Citations

  • A black alumina ceramic powder, a black alumina ceramic body made of it and a process for producing the black alumina ceramic body

    CN107406328A

  • Black aluminum oxide ceramic color agent, and preparation method and applications thereof

    CN109111760A

  • Alumina ceramic as well as preparation method and application thereof

    CN115340367A

  • Black alumina sintered compact and method of manufacturing the same

    JP2008260645A

  • Alumina ceramic toughened with black zirconia and method for manufacturing the same

    JP2013056809A